Republic of Tajikistan : Staff Report for the 2004 Article IV Consultation and Fourth Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Tajikistan's 2004 Article IV Consultation and Fourth Review Under the Poverty Reduction and Growth Facility. Strengthened fiscal discipline and tighter monetary policy have reduced inflation from 40 percent in 2001 to 5.6 percent in 2004. Strong growth in tax revenues and continued expenditure restraint contributed to small fiscal surpluses during the past two years. Nonetheless, progress in a number of priority reform areas envisaged in the Poverty Reduction Strategy Paper has been slow. In particular, the business environment and public and private sector transparency and governance need to be strengthened further.